Typology and distribution of small farms in Europe: Towards a better picture. (June 2018) - Guiomar, N.; Godinho, S.; Pinto-Correia, T.; Almeida, M.; Bartolini, F.; Bezák, P.; Biró, M.; Bjørkhaug, H.; Bojnec, Š.; Brunori, G.; Corazzin, M.; Czekaj, M.; et al.
Highlights: Totally novel classification of regions in Europe according to the role of small farms. Combining structural with economic farm size to obtain a more accurate picture of small farms distribution in Europe today. Identifying the role of small farms in each particular regional context. Detailed NUTS-3 typology of regions in Europe. Contribution to policy targeting through adaptative assessment tools Abstract: The contribution of small farms to local food supply, food security and food sovereignty is widely acknowledged at a global level. In the particular case of Europe, they often are seen as an alternative to large and specialised farms. Assessing the real role of small farms has been limited by a lack of information, as small farms are frequently omitted from agricultural censuses and national statistics. It is also well acknowledged that small farms differ widely, and are distributed according to different spatial patterns across Europe, fulfilling different roles according to the agriculture and territorial characteristics of each region. This paper presents the result of a novel classification of small farms at NUTS-3 level in Europe, according to the relevance of small farms in the agricultural and territorial context of each region, and based on a typology of small farms considering different dimensions of farm size. The maps presented result from an extensive data collection and variables selected according to European wide expert judgement, analysed with advanced cluster procedures. The results provide a fine grained picture of the role of small farms at the regional level in Europe today, and are expected to support further data analysis and targeted policy intervention.